2020
DOI: 10.1101/2020.03.09.983817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IncreasedAPOEε4expression is associated with reactive A1 astrocytes and the difference in Alzheimer Disease risk from diverse ancestral backgrounds

Abstract: up to 70 words)APOEε4 African local genomic ancestry (LA) confers less risk for Alzheimer disease (AD) relative to European LA (LA) carriers. Single nucleus RNA sequencing from AD-APOE4/4 frontal cortex found European LA carriers have a 1.45-fold greater APOEε4 expression (p< 1.8 E10 -313 ) and are associated with a unique A1 reactive astrocyte cluster. This suggests a potential mechanism for the increased risk for AD seen in European LA carriers of APOEε4.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recently, using single nuclei RNAseq on frozen frontal cortex, we found that APOEε4 homozygotes lying on a European local ancestry had significantly higher expression of APOEε4 than APOEε4 homozygotes lying on an African local ancestry 39 , suggesting a significant difference in the regulatory composition of this regions between ancestries. This supports the importance of determining potential regulatory variants differing in the regulatory architecture between local ancestries.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, using single nuclei RNAseq on frozen frontal cortex, we found that APOEε4 homozygotes lying on a European local ancestry had significantly higher expression of APOEε4 than APOEε4 homozygotes lying on an African local ancestry 39 , suggesting a significant difference in the regulatory composition of this regions between ancestries. This supports the importance of determining potential regulatory variants differing in the regulatory architecture between local ancestries.…”
Section: Discussionmentioning
confidence: 98%